IMPROVING STUDENTS’ VOCABULARY IN TRANSACTIONAL TEXT BY USING DOMINO GAME IN SMPN 16 PONTIANAK - Najamuddin, Najamuddin; Sofian, Sofian; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted on the seventh grade student of SMP Negeri 16 Pontianak in academic year 2017/2018. The research was conducted in order to solve the problem of students in vocabulary achievement on transactional text. Most of the students had lack of vocabulary. To achieve the objectives of the research, a classroom action research was conducted. The researcher observed the students’ vocabulary achievement by collecting the data through direct and measurement technique. The tools of data collecting were observation checklist, field note, and test. The test contained 30 questions, and implemented to 30 seventh grade class B students. This research was done in three cycles. The result of data analysis showed that Domino game was a successful technique for improving students’ vocabulary achievement. Observation checklist and field note also showed improvement in teaching learning process. The words in material, which had provided by the teacher as an example in the beginning of the lesson activated students’ background knowledge about materials. Working together in groups when playing Domino game also encouraged the students to remember the new vocabulary, they also became active in class. It can be concluded that the students’ vocabulary achievement by using Domino game technique was improved. Keywords: Vocabulary, Domino game technique, Transactional text